Роль инновационных подходов в образовании и подготовке педагогических кадров - Фазылова, С.С. (My University, 2016)
Relevance.Improving the quality of education, through the introduction of innovative methods and technologies in teaching. Personneltraining.
Keywords: component; innovative; methods; retraining; technologies